Does inferior vena cava respiratory variability predict fluid responsiveness in spontaneously breathing patients?. Issue 1 (December 2015) - Airapetian, Norair; Maizel, Julien; Alyamani, Ola; Mahjoub, Yazine; Lorne, Emmanuel; Levrard, Melanie; Ammenouche, Nacim; Seydi, Aziz; Tinturier, François; Lobjoie, Eric; Dupont, Hervé; Slama, Michel
Abstract Introduction We have almost no information concerning the value of inferior vena cava (IVC) respiratory variations in spontaneously breathing ICU patients (SBP) to predict fluid responsiveness. Methods SBP with clinical fluid need were included prospectively in the study. Echocardiography and Doppler ultrasound were used to record the aortic velocity-time integral (VTI), stroke volume (SV), cardiac output (CO) and IVC collapsibility index (cIVC) ((maximum diameter (IVCmax)– minimum diameter (IVCmin))/ IVCmax) at baseline, after a passive leg-raising maneuver (PLR) and after 500 ml of saline infusion. Results Fifty-nine patients (30 males and 29 females; 57 ± 18 years-old) were included in the study. Of these, 29 (49 %) were considered to be responders (≥10 % increase in CO after fluid infusion). There were no significant differences between responders and nonresponders at baseline, except for a higher aortic VTI in nonresponders (16 cm vs. 19 cm, p = 0.03). Responders had a lower baseline IVCmin than nonresponders (11 ± 5 mm vs. 14 ± 5 mm, p = 0.04) and more marked IVC variations (cIVC: 35 ± 16 vs. 27 ± 10 %, p = 0.04). Prediction of fluid-responsiveness using cIVC and IVCmax was low (area under the curve for cIVC at baseline 0.62 ± 0.07; 95 %, CI 0.49-0.74 and for IVCmax at baseline 0.62 ± 0.07; 95 % CI 0.49-0.75). In contrast, IVC respiratory variations >42 % in SBP demonstrated a high specificity (97 %) and a positive predictive value (90 %) to predict an increase in CO after fluid infusion. Conclusions In SBP with suspected hypovolemia, vena cava size and respiratory variability do not predict fluid responsiveness. In contrast, a cIVC >42 % may predict an increase in CO after fluid infusion.